Understanding attitudes and beliefs regarding COVID-19 vaccines among transitional-aged youth with mental health concerns: a youth-led qualitative study - Andrew Johnson; Daniel Z Buchman; Andrea Levinson; Claire Perry; Nicole Kozloff; Sanjeev Sockalingam; Erin Artna; Alexxa Abi-Jaoudé; Charlotte Wun; Jo Henderson (BMJ Open, 2024)
Background Transitional-aged youth (16–29 years) with mental health concerns have experienced a disproportionate burden of the COVID-19 pandemic. Vaccination is limited in this population; however, determinants of its vaccine hesitancy are not yet thoroughly characterised.Objectives This study aimed to answer the following research question: What are the beliefs and attitudes of youth with mental illness about COVID-19 vaccines, and how do these perspectives affect vaccine acceptance? The study aims to generate findings to inform the development of vaccine resources specific to youth with mental health concerns.Methods A qualitative methodology with a youth engagement focus was used to conduct in-depth semistructured interviews with transitional-aged youth aged 16–29 years with one or more self-reported mental health diagnoses or concerns. Mental health concerns encompassed a wide range of symptoms and diagnoses, including mood disorders, anxiety disorders, neurodevelopmental disorders and personality disorders. Participants were recruited from seven main mental health clinical and support networks across Canada. Transcripts from 46 youth and 6 family member interviews were analysed using thematic analysis.Results Two major themes were generated: (1) factors affecting trust in COVID-19 vaccines and (2) mental health influences and safety considerations in vaccine decision-making. Subthemes included trust in vaccines, trust in healthcare providers, trust in government and mistreatment towards racialised populations, and direct and indirect influences of mental health.Conclusions Our analysis suggests how lived experiences of mental illness affected vaccine decision-making and related factors that can be targeted to increase vaccine uptake. Our findings provide new insights into vaccine attitudes among youth with mental health concerns, which is highly relevant to ongoing vaccination efforts for new COVID-19 strains as well as other transmissible diseases and future pandemics. Next steps include cocreating youth-specific public health and clinical resources to encourage vaccination in this population.